Leaders’ Narratives on Enhancing Academic Results through Soft Skills - Subedi, Netra Bahadur (KMC Research Journal, 2020)
Although the term “soft skill” is new in our context, it has got lots of momentum very recently. Many research works on soft skills have been made worldwide and one important finding says that soft skills are important employability skills (Vasanthakumari, 2019.) Unfortunately, no substantial study has been made on whether soft skills help retain hard skills or not. Therefore, I have attempted to research this less travelled area and the finding is that soft skills help retaining hard skills and strengthening academic results. In the course of my research, I applied narrative inquiry as a research methodology selecting three research participants purposively. After data presentation, as I analyzed the patterns and themes, I got the finding that soft skills are supportive to enhance hard skills.